The anti-metastatic effect of 8-MOP on hepatocellular carcinoma is potentiated by the down-regulation of bHLH transcription factor DEC1. (March 2016) - Xiong, Jing; Yang, Huan; Luo, Wenjing; Shan, Enfang; Liu, Jie; Zhang, Feng; Xi, Tao; Yang, Jian
Graphical abstract: Abstract: Despite progress in diagnostics and treatment of hepatocellular carcinoma (HCC), its prognosis remains poor. 8-Methoxypsoralen (8-MOP), a formerly considered photosensitizing agent, has been reported to induce cell apoptosis in HepG2 cells in a modest way when used alone. In this study, it was demonstrated that 8-MOP inhibited HCC HepG2 cells and SMMC-7721 cells migratory and invasive potentiality, as well as modulated the expression of various EMT-associated genes such as enhancing E-cadherin and reducing N-cadherin, vimentin, α-SMA and MMP9 in a concentration-dependent way. Differentiated embryonic chondrocyte-expressed gene 1, DEC1 (BHLHE40/Stra13/Sharp2), is a basic helix-loop-helix (bHLH) transcription factor that regulates cell growth, differentiation, apoptosis and tumorigenesis. 8-MOP suppressed the expression of DEC1 in a concentration- and time-dependent manner. Overexpression of DEC1 endorsed the HepG2 cells a higher metastatic phenotype, while totally abolished 8-MOP-repressed metastatic capability. In the meanwhile, overexpression of DEC1 promoted EMT process by suppressing expression of epithelial protein and enhancing expression of mesenchymal proteins, while potently antagonized the regulation of EMT-associated genes by 8-MOP. In vivo experiments revealed that the treatment of 8-MOP (5 or 20 mg/kg) resulted in a dose-dependent decreases in the lung metastasis of hepatoma H22-transplanted mice without any obvious toxicity to the organs, as well as increased expression of E-cadherin in lung tissues. Consistently, 8-MOP down-regulated the expression of DEC1 in the lungs of tumor-bearing mice, which further confirms that DEC1 was correlated with 8-MOP-induced anti-metastatic effect. The present findings establish a function for DEC1 in HCC metastatic progression and suggest its candidacy as a novel target for the anti-metastasis effect of 8-MOP.